Dampak Higgs Domino Island dalam Masyarakat (Kajian Dengan Perspektif Sosiologi Hukum) - Nasruddin Khalil Harahap (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2021)
The era of the Industrial Revolution 4.0 has an impact on overall changes in various sectors. Its development has made every country, both developed and developing countries, to improve and renew each other in their respective countries. The development of technology, so can have both positive and negative impacts. One of the developments is the increasing number of online games, both for transactions and non-transactions. The online game that will be studied is the Higgs Domino Island online game. Users or players can make chip/money transactions belonging to other users or players. This research is a field research using the interview method on users/players of the Higgs Domino Island Online. The hope from this research is that the public understands which games are allowed and which are prohibited in the applicable laws and regulations and the government must limit the games that can be used by every citizen by making regulations